Screening of Anxiety and Quality of Life of People with Chronic Diseases at The Bandung City Elderly Posbindu - Ermilda Ermilda; Dedeh Dahliah; Andi Rina Hatta (International Journal Labs, 2025)
As individuals age, their bodies become more susceptible to chronic diseases. The elderly are at a higher risk of developing chronic diseases compared to other age groups. Chronic diseases can have a significant impact on the health and quality of life of the elderly. Elderly individuals with chronic diseases often face psychological challenges, including anxiety, depression, and stress. This study aims to investigate the relationship between anxiety levels and quality of life in elderly individuals with chronic diseases, as well as the significant relationship between anxiety levels in elderly individuals with chronic diseases and quality of life. Data collection in this study utilized the Anxiety Disorder Assessment Scale (HDAS) and the EQ-5D-5L quality of life scale. Based on the results of the Spearman correlation test, with a rho (?) value of p = 0.009 < 0.01 and r = 0.463, it was found that there is a significant relationship between anxiety levels and quality of life in elderly individuals with chronic diseases.